2012
DOI: 10.1371/journal.pone.0036965
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Quantification in Idiopathic Intracranial Hypertension by Spectral Domain OCT

Abstract: ObjectiveTo evaluate 3D spectral domain optical coherence tomography (SDOCT) volume scans as a tool for quantification of optic nerve head (ONH) volume as a potential marker for treatment effectiveness and disease progression in idiopathic intracranial hypertension (IIH).Design and PatientsCross-sectional pilot trial comparing 19 IIH patients and controls matched for gender, age and body mass index. Each participant underwent SDOCT. A custom segmentation algorithm was developed to quantify ONH volume (ONHV) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 33 publications
1
53
0
3
Order By: Relevance
“…Compared with sonography, it is expected to have better accuracy and precision for optic nerve head volume measurements. 27 A systematic review and meta-analysis of the ONSD literature for detection of raised ICP has already been published by Dubourg et al 13 Data were extracted from electronic databases, with manual review of literature and conference proceedings from 1960 up until July 2010. Six studies were included in the meta-analysis, which included 231 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with sonography, it is expected to have better accuracy and precision for optic nerve head volume measurements. 27 A systematic review and meta-analysis of the ONSD literature for detection of raised ICP has already been published by Dubourg et al 13 Data were extracted from electronic databases, with manual review of literature and conference proceedings from 1960 up until July 2010. Six studies were included in the meta-analysis, which included 231 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The development of technologies with which RNFL loss may be quantified, including OCT, scanning laser polarimetry, and confocal scanning laser ophthalmoscopy (CSLO), has been an important landmark in the diagnosis and management of a number of optic nerve diseases. Nevertheless, although these technologies have been used to diagnose and monitor optic disc edema in patients with raised intracranial hypertension, 15,16,18,[32][33][34][35][36][37][38] very few studies have attempted to quantify axonal loss in eyes with papilledema. Using CSLO and automated perimetry, Salgarello et al 34 evaluated eight patients with recently diagnosed papilledema and found a significant correlation between the amount of disc edema and VF loss.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that OCTmeasured peripapillary RNFL thickness can be used to estimate the degree of papilledema and, consequently, to monitor treatment efficacy. [14][15][16][17][18] The presence of optic disc edema, however, artificially increases OCTmeasured RNFL thickness measurements and prevents accurate estimation of peripapillary axonal loss.…”
Section: Introductionmentioning
confidence: 99%
“…Kaufhold et al found that the OCT parameter optic nerve head volume (ONHV) was actually a better measure of ICP compared to RNFL thickness with AUC = 0.835 and AUC = 0.464, respectively [65]. The major flaw with their study, however, is that the ICP measurements were acquired from lumbar puncture (LP) opening pressures that were performed anytime within 0 to 24 months of the OCT scan, which in some cases, resulted in a large time gap between ICP and OCT measurements.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%